Equitable Implementation of Green Infrastructure: An Analysis of the City of Vancouver - Jang, Nicole; Doyon, Andréanne (Canadian Planning and Policy / Aménagement et politique au Canada, 2023)
As climate change continues to pose a threat to human health, cities have turned to nature-based solutions, such as green infrastructure (GI), to lessen the impacts of climate change felt by communities. However, many practitioners are not incorporating equity considerations in GI siting decisions; thus, leaving marginalized and racialized communities to disproportionately bear the impacts of urban environmental issues. In the City of Vancouver, British Columbia, Canada, the GI Branch is investigating ways in which they can apply an equity lens to their work. To aid in their endeavour, this study examines existing challenges to equitably implementing GI, as well as areas for improvement, through a literature review, document and planning tool analysis, and key informant interviews. Drawing from the findings, this paper develops a set of equity criteria, which centre three dimensions of social equity: distributional, recognitional, and procedural equity, to help practitioners operationalize equity in GI project evaluations.